Pengaruh Kualitas Pelayanan Publik terhadap Kepuasan Masyarakat di Kantor Desa Semawung Kecamatan Purworejo Kabupaten Purworejo (STIE Rajawali Purworejo, 2024)
This study aims to determine whether service quality has a positive and significant effect on public satisfaction at the Semawung Village Office, Purworejo District, Purworejo Regency. The data source uses a questionnaire. The population in this study were people who were and/or had taken care of KTP, KK, SKTM, SKCK cover letters, birth certificates, birth certificates, death certificates, land certificates, and others at the Semawung Village Office, Purworejo District, Purworejo Regency in the period from January 1, 2022 to July 31, 2022. The sampling technique was purposive sampling. The number of samples taken was 30 people. The data analysis technique used was simple linear regression analysis, coefficient of determination, and t-test. The results of the simple linear regression analysis showed: a constant of 9.328, a b value of 1.366. The results of the coefficient of determination showed an R square value of 0.736. This means that service quality contributes 73.6% to satisfaction. The results of the t-test show: the calculated t value is greater than the t table (8.837 > 1.701) with a sig value of 0.000 (< 0.05), meaning that there is a positive and significant influence between service quality and public satisfaction at the Semawung Village Office, Purworejo District, Purworejo Regency.